c - SNICKET, LEMONY (b)
In The Ersatz Elevator (Book 6 of A Series of Unfortunate Events), the Baudelaire orphans are placed with wealthy, trendy guardians Jerome and Esmé Squalor on "Dark Street." They discover their friends, the Quagmires, are hidden in an empty elevator shaft by Count Olaf disguised as Gunther before the villains escape.
English